Analysis of Tourist Interest in Event Club Activities in Teripang Village, Riau Islands, Indonesia - Indah Andesta; Nur Atika (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: The aim of this research is to analyze of tourist interest to event club activity in Teripang Village to develop tourism attraction in Teripang Village. Methods: The method used is descriptive qualitative using in-depth interviews, observation, literature studies and surveys to tourists. The data obtained are presented in descriptive form. Results: The result of this research is natural soap bar has the high of tourist interest both edu-tourism and memorable experience. The activity show the same with tourist expectation and tourist interest to revisit to Teripang Village and doing edu-tourism like natural soap bar. While, tote bag painting is event club activities in this has lack of tourist interest in Teripang Village. Through this research, management of Teripang village knows that natural soap bar is edu-tourism activity that has high demand.    Contribution:  This research provides information to Teripang Village management for event club activities that are of interest to tourists and event club activities that lack interest.